Living alone predicts mortality in patients with ischemic stroke before 70 years of age: a long-term prospective follow-up study. Issue 1 (December 2016) - Redfors, Petra; Isaksén, Daniella; Lappas, Georgios; Blomstrand, Christian; Rosengren, Annika; Jood, Katarina; Jern, Christina
Abstract Background Living alone is associated with increased mortality after myocardial infarction but little data is available about whether this applies to prognosis after stroke. We aimed to examine the association between living situation and long-term mortality in patients with ischemic stroke and a control group, and to explore whether this association is modified by patient gender. Methods This is a prospective case-control study of 600 patients with ischemic stroke before 70 years of age and 600 age- and sex-matched controls who have been included in the Sahlgrenska Study on Ischemic Stroke. Mortality data were collected through national registers and medical records. We used Cox regression models for identifying predictors of mortality. Results In the entire sample, mean age was 57 years, proportion of males 64 %, proportion living alone 28 %, and median follow-up 8.6 years. Mortality rates were 36 % among patients living alone, 17 % among cohabitant patients, 15 % among controls living alone, and 9 % among cohabitant controls. Living alone was an independent predictor of all-cause mortality in cases after adjustment for stroke severity, stroke subtype, and vascular risk factors including physical activity, alcohol consumption, and socioeconomic status. A significant interaction was found between gender and living situation; the adjusted hazard ratio for mortality was 3.47 (95 % Confidence Interval 2.13–5.65) in male patients living alone, whereas no significant association was observed in women. Living alone was also a predictor of vascular mortality among cases and of all-cause mortality among controls. Conclusions Living alone is associated with increased long-term mortality after ischemic stroke in men. Further prospective studies are needed to confirm the observed gender difference and to identify modifiable factors underlying this increased risk.